Characteristics of the thermal environment, air quality, and passenger comfort in the underground transfer space of metro stations in Beijing. (1st November 2022) - Lin, Chunxiang; Wu, Liming; Xia, Haishan; Zhen, Meng; Shen, Chen; Zhu, Jinjin; Li, Xinyi
Abstract: With the increase in Beijing's metro mileage and passenger numbers, it is becoming especially necessary to investigate the indoor environment and passenger comfort of metro stations. In this study, the transfer spaces in the top seven transfer stations with the largest passenger flow within the Beijing metro system were selected for conducting indoor environment (thermal environment and air quality) measurements and a subjective comfort survey of over 600 passengers. The results showed that the thermal environment and air quality experienced by passengers changed dynamically with the passenger transfer process. Indoor temperature and relative humidity (RH) were affected by not only aboveground weather changes but also station depth, and the indoor temperature in winter was more comfortable than that in summer. The trend in subjective feelings of passengers' thermal comfort was similar to that of the relative warmth index (RWI) evaluation of seven transfer stations during the measurement periods, and passengers' thermal comfort during the summer morning rush hours was not ideal but was slightly hot overall. Although the concentrations of carbon dioxide (CO2 ) and particulate matter (PM: including PM2.5 and PM10 ) met the indoor air quality maintenance standards, the percentage of passengers uncomfortable with the air quality exceeded 80% during both seasons, and the centralized tendency in winter was very uncomfortable. Passengers are very concerned about air quality, and their subjective feelings are relatively susceptible to psychological factors. Regarding the overall comfort trend, passengers' subjective feelings of comfort during the morning rush hours in summer and winter were both "slightly uncomfortable". This paper provides a valuable reference for further research on environmental, health, and energy saving issues in metro stations and presents reliable primary research data for the design and operation management of ventilation and air conditioning systems in metro stations. Graphical abstract: Image 1 Highlights: The thermal environment and air quality experienced by passengers changed dynamically with the transfer process. The thermal comfort of the metro transfer space in winter is better than that in summer. Passengers' subjective perception of air quality is more likely to be affected by psychological factors. Passengers feel slightly uncomfortable on the overall comfort of the metro transfer space in summer and winter.